How to break free: HIV-1 escapes from innovative therapeutic approaches - Magro, Gloria; Calistri, Arianna; Parolin, Cristina (Frontiers in Virology, 2022)
With nearly 38 million of people worldwide living with HIV-1 and no definitive cure available after almost 40 years of research, AIDS is still a major global Public Health issue. Modern antiretroviral therapies can achieve viral replication suppression to undetectable levels, thus allowing an almost normal life to HIV-1 infected individuals. However, the virus cannot be fully eradicated. This may lead over time to the accumulation of mutations in the viral genome and, eventually, to the emergence of drug-resistant viruses, which may affect the efficacy of the therapy and the patient’s quality of life. To overcome some of the limitations of the standard antiretroviral therapy, innovative therapeutic approaches such as “shock and kill” and immunotherapies, as well as technologies based on RNA interference and CRISPR-Cas9 genome editing are under investigation. Nevertheless, the virus may find a way to break free even from these novel strategies. In this review, we focus on the mechanisms that enable HIV-1 escape from some of the most advanced therapies and discuss some of the challenges to prevent this issue.